Reminiscing traditional masjid architecture in a contemporary world: The making of Masjid Al-Falah - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Mohd Yunus, Yahaya; Ali, Maisarah; Ibrahim, Mansor (Kulliyyah of Architecture and Environmental Design, IIUM, 2016)
This article is written based on an actual project under Prime Minister's Grant to extend an existing village masjid - Al-Falah Masjid at Belukar Luas, Ketereh, Kota Bharu. The existing masjid was design based on an Indian architecture with domes, arches, and finials. Given as Kulliyyah of Architecture and Environmental Design (KAED), IIUM's community project, the team appointed for the project from day 1 to completion, had embarked on the search for an appropriate masjid architecture. Literature review and case study visits were conducted on the traditional masjid of Kelantan and emerge a proposal of a Nusantara Masjid type to house the new 500 qariah from the existing 300. There were many challenges in its implementation. The project cost has been the bottom line for construction where changes have to be made to keep the project to below RM1 million. The outcome, however, is a blessing to both the team and the qariah of the masjid where the spirit of the traditional past can be relived in this opportune project despite all odds.